Trends and Directions of Gamification Research in Mathematics: Systematic Literature Review - I Ketut Lokasanti; Ketut Agustini; I Gde Wawan Sudatha; Anak Agung Adi Wiryya Putra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Mathematics education plays a crucial role in equipping students with the skills necessary for the 21st century, such as critical thinking and problem-solving abilities. However, many students perceive mathematics as a challenging and tedious subject, which ultimately leads to a decline in their motivation and learning outcomes. Consequently, the application of gamification as an alternative method in mathematics instruction has demonstrated significant potential for enhancing student engagement and learning results. This research aims to investigate the impact of gamification in mathematics learning, as well as the trends associated with its implementation. Findings from prior studies indicate that gamification, whether digital or non-digital, can enhance motivation, reduce mathematics-related anxiety, and deepen the understanding of mathematical concepts. Digital educational games, along with the use of non-digital playing cards, have proven effective in improving student engagement and comprehension of mathematics across various educational levels. Adaptive learning systems that utilize artificial intelligence (AI) also exhibit substantial potential in providing personalized learning experiences tailored to the abilities of individual learners. This article examines 13 prominent journals selected following a rigorous elimination process utilizing the systematic literature review methodology. This process will occur from 2015 until 2025. The objective of this systematic approach is to evaluate and analyze pertinent, high-quality literature to enhance comprehension of the subject matter. The PRISMA approach is utilized to choose articles based on the established inclusion and exclusion criteria to get pertinent literature. Nevertheless, the challenges faced include the creation of gamification that is both more immersive and relevant to real-life contexts. Further research is required to explore the implementation of more pertinent gamification elements, such as challenges based on real-world situations and aspects of robotics, as well as the influence of social and emotional factors on the effectiveness of gamification in mathematics education. Thus, this study contributes to identifying the potential and shortcomings in the application of gamification within the field of mathematics education.